PENDIDIKAN ISLAM ERA RASULULLAH SEBAGAI REFLEKSI PENDIDIKAN ISLAM KEKINIAN - Muhammad Amin (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2018)
The Islamic education in the era of Rasulullah was known as an ideal Islamic education even though it wascarried out in circumstances and limitations. Islamic education in the era of Muhammad has proven successfulin giving birth to a golden generation in the Islamic world. This is inversely proportional to contemporary Islamiceducation which with various facilities and adequate learning media has given birth to some individuals whoembarrass the Islamic world itself. This paper aims to reflect on the era of the Prophet’s education to improvethe current state of Islamic education, ranging from educational institutions, educational goals, educationmethods to Islamic education material itself. With the hope of minimizing corruption and immoral acts committedby individuals who are alumni of Islamic education institutions and can revive the marwah of Islamic educationin the proper and proper position as aspired by the Prophet.Key Word: Pendidikan Islam, Era, Refleksi, Kekinian AbstrakPendidikan Islam di era Rasulullah dikenal sebagai pendidikan Islam yang ideal walaupun dilaksanakan dalamkeadaan serta keterbatasan. Pendidikan Islam era Rasulullah telah terbukti berhasil melahirkan generasi emasdalam dunia Islam. Hal itu berbanding terbalik dengan pendidikan Islam kekinian yang dengan berbagai fasilitasdan media pembelajaran yang memadai telah melahirkan beberapa oknum yang membuat malu dunia Islam itusendiri. Tulisan ini bertujuan untuk merefleksikan pendidikan era Rasulullah untuk memperbaiki keadaan duniapendidikan Islam kekinian, mulai dari lembaga pendidikan, tujuan pendidikan, metode pendidikan sampai padamateri pendidikan Islam itu sendiri. Dengan harapan dapat meminimalisir tindakan korupsi dan asusila yangdilakukan oleh oknum yang merupakan alumni lembaga pendidikan Islam dan dapat mengangkat kembalimarwah pendidikan Islam pada posisi yang seharusnya dan selayaknya sebagaimana yang dicita-citakanRasulullah.Kata Kunci: Pendidikan Islam, Era, Refleksi, Kekinian